Bol Soc Esp Hidrol Med 2018
DOI: 10.23853/bsehm.2018.0605
|View full text |Cite
|
Sign up to set email alerts
|

Prevention and Therapy of Type 2 Diabetes-What Is the Potential of Daily Water Intake and Its Mineral Nutrients?

Abstract: We aim to present an overview of the possible influence of drinking water in general and mineral water in particular in improving glycemic parameters in persons with or without type 2 diabetes. We performed a literature search that produced 15 randomized controlled trials (RCTs) on this topic with mainly small sample sizes. We also discuss relevant observational and animal studies as well as the effects of important supplements in mineral water such as hydrogencarbonate and magnesium. There is low evidence for… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
7
0
2

Year Published

2018
2018
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(9 citation statements)
references
References 24 publications
0
7
0
2
Order By: Relevance
“…Additionally, a significant association between hypomagnesaemia and new-onset diabetes after kidney transplantation (NODAT), in kidney transplant recipients, for both adult and pediatric patients has been indicated. Moreover, murine studies have shown that the maternal hypomagnesaemia is associated with diabetes mellitus, insulin resistance, dyslipidemia, metabolic syndrome, depression, impaired placental development, impaired fetal growth and increased mortality [28][29][30][31][32][33][34][35][36][37][38][39][40][41]. Bottled water may be an essential and inexpensive source of magnesium and other minerals.…”
Section: Discussionmentioning
confidence: 99%
“…Additionally, a significant association between hypomagnesaemia and new-onset diabetes after kidney transplantation (NODAT), in kidney transplant recipients, for both adult and pediatric patients has been indicated. Moreover, murine studies have shown that the maternal hypomagnesaemia is associated with diabetes mellitus, insulin resistance, dyslipidemia, metabolic syndrome, depression, impaired placental development, impaired fetal growth and increased mortality [28][29][30][31][32][33][34][35][36][37][38][39][40][41]. Bottled water may be an essential and inexpensive source of magnesium and other minerals.…”
Section: Discussionmentioning
confidence: 99%
“…Physical therapy promoted the activation of metabolism by reducing adipose tissue and increasing muscle tissue [29,30]. Improvement of the studied parameters was favored by the use of drinking balneotherapy due to the coordination of enteroinsular interactions and a decrease in IR [31,32]. The inclusion of vitamins and minerals in the therapeutic program is based on their antioxidant abilities and their importance in coordinating metabolic processes [33,34].…”
Section: Discussionmentioning
confidence: 99%
“…Auch die Inzidenz/Mortalität von Diabetes mellitus oder metabolischem Syndrom wurde mit der Wasserhärte in Verbindung gebracht [13]. Rosborg et al beschreiben in einer umfangreichen Zusammenfassung der verfügbaren epidemiologischen Untersuchungen weitere mögliche Zusammenhänge zwischen Mineralstoffgehalt des Trinkwassers und Krankheitsrisiken [14].…”
Section: Der Einfluss Der Wasserhärteunclassified